Beijing Consensus: alternative for Africa's development challenges? The case for Zimbabwe - Nyere, Shepherd (Research of GSB, 2018)
The research aimed to study whether the Beijing Consensus, a Chinese development model is an alternative development model for Africa. The study used Zimbabwe's plan to collateralise its natural resources mainly minerals under the Angola Model strategy as a test case. Zimbabwe's economic revival is currently ransomed by an unsustainable debt that has blocked external financial aid from its traditional donors and the western world. This is against the background that since the 1989, economist John Williamson's economic and policy recommendations known as the Washington Consensus became generally accepted as the most effective model by which developing countries could spur growth. This model based around ten policy recommendations embracing ideals of free-market capitalism that include open trade policies, privatisation and deregulation provided a prescription for development in the less developed countries. However, its implementation had mixed results such as multiple currency crisis, stagnation and recession during the financial turmoil of the 1990s and the most recent and more severe 2007 financial crises that led to the collapse of several nations' economic systems. This further eroded the confidence in the Western neoliberal economic model leaving the world calling for an alternative development model. By the turn of the century, a new strategy driven by China that has been defined by Joshua Cooper Ramo as the Beijing Consensus surfaced as a challenge to the Washington Consensus. This model is described as pragmatic, recognises the need for flexibility in solving multifarious problems. The model sounding warning bells for a post-Washington Consensus is inherently focused on innovation and emphasise equitable development driven by the central government has quickly gained appeal within the developing world challenging the Washington Consensus' antiquated policies. This exploratory research case study using primarily available literature on the subject sought to determine whether the Beijing Consensus is an alternative development model for Africa. To help synthesise the subject, Zimbabwe was used as a case study through primarily the "Angola model"- a Chinese strategy for resource-rich countries that are unable to guarantee loan repayments. Apart from the "Angola model", the study looked at the overall impact of the Chinese investments in Zimbabwe and Africa in general. The findings of the study has revealed while the Angola Model may have worked for Angola and other oil producing nations, it however will not benefit Zimbabwe as it is not geared in solving the current debt crisis. The results also show that while the Beijing Consensus may not actually be a consensus, it is currently an alternative for African nations as it presents an array of choices. It however does not seem to replace the Washington Consensus as a widely accepted consensus model for development but it has the right ingredients from a starting point to develop into an alternative model.